Hubungan Chrononutrition Terhadap Status Gizi, Lingkar Lengan Atas, dan Anemia pada Remaja Putri: The Relationship Between Chrononutrition with Nutritional Status, Mid Upper Arm Circumference and Anemia in Adolescent Girl - Pibriyanti, Kartika; Mufidah, Indahtul; Luthfiya, Lulu'; Rooiqoh, Qothrunnadaa Fajr; Pinasti, Ladyamayu; Amala, Nur; Claresta, Ivena; Nurohmi, Susi (Amerta Nutrition, 2025)
Background: The Adolescents are currently facing the triple burden, which includes undernutrition, overnutrition or obesity, and micronutrient deficiencies. The nutritional status of adolescents was influenced by chrononutrition. Chrononutrition has a significant relationship with nutritional status. However, there are no studies in Indonesia that specifically examine the relationship between chrononutrition and nutritional status, Mid Upper Arm Circumference (MUAC), and anemia in adolescent girls. Objectives: This study aimed to analyze the relationship between chrononutrition and nutritional status in adolescents. Methods: This study was cross-sectional, that was conducted in Senior High School in Widodaren, Ngawi, in August until september 2024. The population in this study were teenager aged 14-19 years with a sampel size of 100 respondents calculated using the Lemeshow formula. The independent variable was chrononutrition namely breakfast skipping, evening eating and night eating. The chrononutrition was obtained using Chrononutrition Profile Questionnaire. Meanwhile the dependent variable was nutritional status using Body Mass Index/Age, anemia level using hemoglobin and chronic energy deficiency level which was obtained by mid upper arm circumference. The data was analyzed by chi square and fisher. Results: There was a relationship between chrononutrition namely breakfast skip (p-value=0.046), night eating (p-value=0.016), and evening eating (p-value=0.01) with nutritional status. There was relationship between chrononutrition namely breakfast skipping (p-value=0.003), night eating (p-value=0.001) and evening eating (p-value=0.03) with Anemia in Adolescent Girl. There was no relationship between chrononutrition namely breakfast skipping, and evening eating with MUAC in Adolescent girl, but there was relationship between night eating with MUAC. Conclusions: There was relationship between chrononutrition, namely breakfast skipping, night eating and evening eating with nutritional status and anemia. There was relationship between night eating with chronic energy deficiency. Meanwhile there was no relationship between chrononutrition, namely breakfast skipping and evening eating with chronic energy deficency.